Surface engineering as a potential strategy to enhance desiccation tolerance of beneficial bacteria - Wang, Yuanyuan; Liu, Lei; Hou, Shuai (Frontiers in Microbiology, 2025)
Desiccation can diminish the viability of beneficial bacteria by over 90%, threatening their effectiveness in agricultural productivity and probiotic applications. Bacterial surface engineering, already proven to combat acidic environments and oxidative damage, offers promising avenues for mitigating desiccation stress. This Perspective explores and adapts these approaches—spanning bioinspired coatings, encapsulation methods, and nanotechnology—to significantly improve bacterial survival under dehydration. By slowing water loss, preserving membrane integrity, and minimizing oxidative damage, surface engineering paves the way for scalable and effective strategies to bolster bacterial resilience in demanding environments.